2007
DOI: 10.1002/adsc.200600557
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on ortho‐Oxidation of Phenols with Dioxygen Mediated by Dicopper Complex: Hints for a Catalyst with the Phenolase Activity of Tyrosinase

Abstract: Theoretical studies on the chemo-and regioselective ortho-oxidation reaction of phenols mediated by a biomimetic (m-h 2 :h 2 peroxo)dicopper(II) complex were performed using unrestricted hybrid density functional theory (UB3LYP) calculations, with the aim of providing a guide for the development of new bio-inspired catalysts with the phenolase activity of tyrosinase. Energetic, structural, and electronic analyses suggested the involvement of a side-on (m-h 2 :h 2 )-Cu 2 O 2 complex as an active intermediate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, apart from the equilibrium between the µ-η 2 :η 2 -peroxo and bis(µoxo) isomers, the reliability of B3LYP relative energies has been substantiated by previous studies. 17,35 After this digression on the relative stability of the µ-η 2 :η 2peroxo and of the bis(µ-oxo) species, we return to the mechanism of aromatic hydroxylation by describing intermediate g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, apart from the equilibrium between the µ-η 2 :η 2 -peroxo and bis(µoxo) isomers, the reliability of B3LYP relative energies has been substantiated by previous studies. 17,35 After this digression on the relative stability of the µ-η 2 :η 2peroxo and of the bis(µ-oxo) species, we return to the mechanism of aromatic hydroxylation by describing intermediate g.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, beside a recent theoretical study focused only on the O-insertion step of the reaction pathway for the aromatic ortho-hydroxylation of phenoxide in a model system, 17 a detailed and complete quantum-mechanical description of the mechanism of the intramolecular aromatic hydroxylation, from the initial Cu I species to the hydroxylated product, is still missing. In the present study we try to fulfill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…However, as reported by Cramer [1112 78], it is necessary to point out that the equilibrium μ-η 2 :η 2 -peroxo/bis(μ-oxo) is artificially displaced towards the peroxo species by hybrid functionals, such as the B3LYP functional, due to unbalanced correlation corrections [1112]. In spite of that, previous calculations agree in considering that the μ-η 2 :η 2 -peroxo species is the active species in the hydroxylation process studied here [3840 7980]. …”
Section: Resultsmentioning
confidence: 52%
“…In particular, there are detailed studies of pMMO complexes [3536], showing why they are suitable for the conversion of methane to methanol [37]. On the other hand, several theoretical studies have analyzed the inter- and intramolecular hydroxylation of aromatic rings [3846]. Most of these studies agree that the aromatic hydroxylation takes place through a peroxo group side-on to the Cu 2 O 2 core.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase model systems that selectively produce aromatic hydroxylation products are available; however, mechanistic pathways are scarce, still not fulfilling all the queries about this type of model mimetic of the tyrosinase, however being in crescendo recently . There are important theoretical contributions reporting the oxidation of external substrates and on hydroxylation of the ligand. , Starting from the work of Karlin et al, a thorough analysis of the ligand hydroxylation has revealed part of the mechanism , and given insight into the reaction pathway mechanism of an intramolecular aliphatic hydroxylation process and also aromatic as well as non-intramolecular aromatic hydroxylation.…”
Section: Introductionmentioning
confidence: 99%